Pharmacokinetics and Immunogenicity of Frunevetmab in Osteoarthritic Cats Following Intravenous and Subcutaneous Administration - Walters, Rodney R.; Boucher, Joseph F.; De Toni, Flavia (Frontiers in Veterinary Science, 2021)
Osteoarthritis and other degenerative joint diseases are common causes of chronic pain in cats. Frunevetmab is a felinized monoclonal antibody that binds to nerve growth factor (NGF) and provides relief from pain by blocking the receptor-mediated signaling cascade induced by NGF. Results from three studies were combined to provide an overview of frunevetmab pharmacokinetics (PK) and immunogenicity. The objective of the first study was to establish the pharmacokinetic parameters resulting from intravenous (IV) and subcutaneous (SC) administration of frunevetmab to the feline patient population at 3 mg/kg. Ten adult cats with naturally-occurring osteoarthritis were administered frunevetmab in a crossover design at 28 day intervals. Non-compartmental pharmacokinetic analysis of the plasma concentration-time data showed that the half-life was 10.1 ± 1.9 days after IV dosing and the SC bioavailability was 60.3% ± 15.8% with maximum drug levels observed at 3-7 days after dosing. Plasma samples were collected at approximately 28 days after dosing during two field safety and effectiveness studies of cats with degenerative joint disease. The doses ranged from 1.0-2.8 mg/kg; 2 or 3 doses were administered either SC/IV, SC/SC, or SC/SC/SC. The data from these studies along with the data from the laboratory pharmacokinetic study were analyzed using nonlinear mixed-effects (NLME) modeling. The model closely predicted the trough concentrations from the two field studies, including the IV treatment in the pilot field study. The trough concentrations were predicted to be close to steady-state after 2 doses. A second objective was to determine the incidence and clinical relevance of frunevetmab immunogenicity. A three-tier anti-drug antibody assay (screen, confirm, titer) was developed and validated. Immunogenicity was assessed in 259 frunevetmab-treated animals enrolled in the two field studies. Only 4 of these animals (1.5%) appeared to develop immunogenicity to frunevetmab. None of the four exhibited adverse events attributed to immunogenicity and no impact on drug levels or efficacy was observed in three of the animals. In the placebo animals, 2.3% (3/131) appeared to develop treatment-emergent immunogenicity. Overall, frunevetmab administration resulted in a very low incidence of treatment-emergent immunogenicity with no safety findings and minimal effect on drug exposure and efficacy.